The process of halal food certification in Malaysia : an analytical study - Nurul Aznira binti Yahya (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research attempts to study and understand the issues on Malaysian ÍalÉl food certification from both SharÊÑah and technical perspectives. It involves the discussion on the internal and external factors that influence the implementation of Malaysian ÍalÉl food certification. In fact, the process of ÍalÉl certification and the misuse of the ÍalÉl logo and certificate have significant relationship with the authenticity of the ÍalÉl food itself. Overall, the process of Malaysian ÍalÉl certification complies with the SharÊÑah, however some weaknesses should be overcome. The finding shows that the application of Malaysian ÍalÉl certification must be seriously implemented by all parties, whether the authorities, consumers or manufacturers. In other words, it is high time to enforce ÍalÉl certification usage on those who want to be involved in food business in order to give full confidence to consumer and preserve MaqÉÎid SharÊÑah. This is because the food industry is often unaware of the requirements of the Muslim consumers. Moreover, it is relevant as an alternative to solve recent issues on food products. As a result, the knowledge of Fiqh consumerism is needed to practice as a new mechanism to cope with ÍalÉl issues. Then, Muslim researchers should be urged to explore this area of study in order to protect Muslim consumers when choosing food for their consumption.